DEVELOPING AND USING ARTIFICIAL INTELLIGENCE APPROACHES IN RESPONSIBLE WAY - Rizwan Hameed; Ali Zamin; Dr. Faisal Rehman (International Journal of Contemporary Issues in Social Sciences, 2024)
Artificial intelligence (AI) have significant ramifications on diverse facets of society, including schooling, instructional methodologies, and the repercussions of the pandemic. This research delves at the ethical ramifications of artificial intelligence (AI), with a particular focus on the significance of fairness, transparency, accountability, and explain-ability as fundamental principles for AI systems within educational and instructional contexts. The current global pandemic has underscored the need of integrating artificial intelligence into the educational realm and pedagogy, in order to effectively tackle several obstacles like remote learning, health monitoring, and personalized educational approaches. This study also conducts investigation the role of artificial intelligence in addressing the problems presented by the epidemic and enhancing educational outcomes, highlighting its potential advantages while recognizing its constraints. Real-world case studies provide valuable insights into both successful and difficult practices in the field of artificial intelligence, underscoring the need of aligning artificial intelligence development with interests and human values. The research also examines the involvement of governmental bodies, corporate sectors, and academic institutions in the establishment of an ethical and responsible artificial intelligence (AI) framework. The text provides predictions on the future direction of artificial intelligence (AI) improvement and emphasizes the difficulties associated with achieving a careful equilibrium between technological advancements and ethical responsibilities. The research highlights the need of a collective commitment to harness the promise of artificial intelligence (AI) while guaranteeing its compatibility with several sectors, including education, finance, pandemic response, and healthcare.